2020
DOI: 10.17816/brmma50523
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological features of manifestations of Wolf – Parkinson – White syndrome in men of draft age with increased dysplastic stigmatization

Abstract: Abstract. Clinical and epidemiological and electrocardiographic features of Wolf Parkinson White syndrome in men of military age were studied. The study was a retrospective study with a solid sample of patients. Of the 1,9056 men residents of St. Petersburg between the ages of 18 and 27, Wolf-Parkinson-White syndrome was identified in 107 (0,56%) people. The disease was asymptomatic in 38 (35,5%) patients. All identified individuals with Wolf Parkinson White syndrome, in addition to asthenic Constitution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Correct relaxation training for PD patients can reshape the motor cortex system and strengthen the function of the sensory-motor system. 7 Some scholars used a parallel cross design to study the short-term therapeutic effect of whole-body vibration therapy on the motor function of 40 patients with PD. The results showed that stiffness and tremor were significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Correct relaxation training for PD patients can reshape the motor cortex system and strengthen the function of the sensory-motor system. 7 Some scholars used a parallel cross design to study the short-term therapeutic effect of whole-body vibration therapy on the motor function of 40 patients with PD. The results showed that stiffness and tremor were significantly improved.…”
Section: Discussionmentioning
confidence: 99%